2000
DOI: 10.1086/315692
|View full text |Cite
|
Sign up to set email alerts
|

Acute Serogroup A Streptococcal Shock: A Porcine Model

Abstract: To elucidate the pathophysiology of acute shock caused by serogroup A streptococci (GAS), GAS were given intravenously to 25 pigs. Short-time infusions of GAS (n=11) caused variable and unpredictable responses. A continuous infusion of 5x108 cfu/kg/h (n=8) caused pulmonary hypertension, arterial hypotension, and reduced cardiac output and liver perfusion, progressing to circulatory shock within 2-4 h. Halving the infusion rate (n=6) induced a more gradual development of shock and doubled the mean survival time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Necrotic fibers that had lost their striations appeared in small clumps; the cytoplasm of the individual cells was vacuolated and hypereosinophilic (Fig. 1) Bacterial counts in infected tissues other then the CNS (Table 1) confirmed that Streptococcus iniae type II is responsible for an overwhelming septic disease characterized by large numbers of live bacteria, in accordance with similar models described in warmblooded animals (Saetre et al 2000, Yuste et al 2002. The histopathological findings of the viscera were consistent with acute bacterial infection: there was mild to moderate centrilobular hepatitis with histiocytic infiltration in the liver; hyaline droplets were observed in the cytoplasm of tubular cells in the kidneys, and there was mild lymphocyte depletion of interstitial tissue; and there was severe congestion in the spleen.…”
Section: Resultssupporting
confidence: 80%
“…Necrotic fibers that had lost their striations appeared in small clumps; the cytoplasm of the individual cells was vacuolated and hypereosinophilic (Fig. 1) Bacterial counts in infected tissues other then the CNS (Table 1) confirmed that Streptococcus iniae type II is responsible for an overwhelming septic disease characterized by large numbers of live bacteria, in accordance with similar models described in warmblooded animals (Saetre et al 2000, Yuste et al 2002. The histopathological findings of the viscera were consistent with acute bacterial infection: there was mild to moderate centrilobular hepatitis with histiocytic infiltration in the liver; hyaline droplets were observed in the cytoplasm of tubular cells in the kidneys, and there was mild lymphocyte depletion of interstitial tissue; and there was severe congestion in the spleen.…”
Section: Resultssupporting
confidence: 80%
“…In neonatal sepsis or direct lung injury, an immediate increase in circulating inflammatory cytokines, including TNF-␣, IL-1␤, IL-6, and IL-10 (11,37,49) triggers second messenger pathways favoring contraction and smooth muscle proliferation (8). Cyclooxygenase (COX) pathway metabolites are implicated in increased pulmonary vascular tone.…”
mentioning
confidence: 99%
“…In porcine models of endotoxemia, it has been reported that the primary hemodynamic effect of LPS infusion is an increase in pulmonary artery pressure and an increase in systemic vascular resistance, followed by a reduction in cardiac output (CO) [23][24][25][26]. In porcine endotoxemia, an increase in pulmonary vascular resistance is also typical [27], which indicates that the porcine pulmonary circulation is very sensitive to vasoconstrictors, or that it produces considerable amounts of vasoconstrictors such as endothelin-1.…”
Section: Discussionmentioning
confidence: 99%